2018
DOI: 10.1186/s11671-017-2427-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization-Inspired Synthesis of Cerium-Doped Carbonaceous Nanoparticles for Highly Hydroxyl Radical Scavenging Activity

Abstract: Cerium oxide nanoparticles recently have received extensive attention in biomedical applications due to their excellent anti-oxidation performance. In this study, a simple, mild, and green approach was developed to synthesize cerium-doped carbonaceous nanoparticles (Ce-doped CNPs) using bio-mineralization of bull serum albumin (BSA) as precursor. The resultant Ce-doped CNPs exhibited uniform and ultrasmall morphology with an average size of 14.7 nm. XPS and FTIR results revealed the presence of hydrophilic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The hydroxyl radical scavenging activities of buckwheat flavonoid nanoemulsion and suspension and the ascorbic acid solution samples were measured as previously reported [ 19 , 20 ]. In brief, FeSO 4 solution (2.5 mM, 1 ml) was added to the samples and then H 2 O 2 (2.5 mM, 1 ml) and salicylic acid (2.5 mM, 1 ml) were added successively.…”
Section: Methodsmentioning
confidence: 99%
“…The hydroxyl radical scavenging activities of buckwheat flavonoid nanoemulsion and suspension and the ascorbic acid solution samples were measured as previously reported [ 19 , 20 ]. In brief, FeSO 4 solution (2.5 mM, 1 ml) was added to the samples and then H 2 O 2 (2.5 mM, 1 ml) and salicylic acid (2.5 mM, 1 ml) were added successively.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that CeNPs show an auto-regeneration process, whereby nanoparticles regenerate the Ce +3 oxidation state atoms from oxidized Ce +4 atoms (during the superoxide radical dismutation process), within a few days, which further makes CeNPs ready to neutralize another superoxide radical. Although some initial studies have reported that CeNPs could also scavenge hydroxyl radicals, however, any conclusive data was not shown as their EPR data suggest that CeNPs does not neutralize hydroxyl radicals (Heckert et al, 2008b; Zou et al, 2018). Our group has found that CeNPs have a high affinity for superoxide radicals and therefore eliminate them efficiently.…”
Section: Antioxidant Nanozymesmentioning
confidence: 99%
“…Centrifuged agglomerated chondrocytes were fixed by 3% glutaraldehyde for 24 h. Osmium tetroxide was used to stabilize the phospholipid membranes of cells and organelles. The next item was dehydrated by a series of ethanol concentrations (50%, 70%, 80%, 90%, 100%) for 10‐min intervals, and then the samples were embedded in resin and sliced for toluidine blue staining (0.5%) (Zou et al, 2018). Images were captured by a Hitachi H‐7650 Transmission Electron Microscope (Hitachi, Japan).…”
Section: Methodsmentioning
confidence: 99%